Correlations between History of Contact with Infected Person and Measles Vaccination Status on the Risk of Measles Incidence in Children: Meta-Analysis - Ervia Fahma Dhony; Bhisma Murti; Hanung Prasetya (Journal of Epidemiology and Public Health, 2024)
Background: Measles is a disease that can be prevented by immunization (VPD), which is highly contagious and often causes widespread outbreaks and can cause lifelong complications and death. Some evidence suggests that the risk of measles is due to contact history and vaccine status. This study aims to estimate the magnitude of the relationship between contact history and vaccine status with the incidence of measles in children, through a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This research is a systematic review and meta-analysis with PICO as follows, Population: children. Intervention: contact history, vaccine status. Comparison: no contact history, no vaccine. Outcome: measles. The articles used in this research were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the keys "History contact" AND "Vaccine" OR "Vaccinated" OR "Immunization" AND "Measles" AND "Children. The included articles were full-text with a case-control study design from 2012 to 2023 and reported the adjusted Odds Ratio (aOR) in multivariate analysis. Article selection was carried out using the PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 8 case-control studies involving the African continent and the Asian continent were selected for meta-analysis. Children with a history of contact have an increased risk of developing measles 4.38 times compared with children without a history of contact, and this relationship is statistically significant (aOR=4.38; 95% CI=1.36 to 14.09; p= 0.010). Children who had been given the measles vaccine had a reduced risk of getting measles 0.30 times compared to children who had not been given the measles vaccine, and this result was statistically significant (aOR= 0.30; 95% CI= 0.22 to 0.40; p< 0.001).Conclusion: Contact history statistically significantly increases the risk of getting measles in children, vaccine statistically significantly reduces the risk of getting measles in children. Keywords: Contact history, vaccine status, measles, children.